2015
DOI: 10.1007/s00138-015-0660-7
|View full text |Cite
|
Sign up to set email alerts
|

Enforcing consistency constraints in uncalibrated multiple homography estimation using latent variables

Abstract: Springer is a green publisher, as we allow self-archiving, but most importantly we are fully transparent about your rights. Abstract An approach is presented for estimating a set of interdependent homography matrices linked together by latent variables. The approach allows enforcement of all underlying consistency constraints while accounting for the arbitrariness of the scale of each individual matrix. The input data is assumed to be in the form of a set of homography matrices individually estimated from imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, just because the residual error for consistent homographies may be slightly higher does not mean that consistent homographies are less accurate. On the contrary, experiments conducted in [8,9,32] demonstrate that enforcing consistency results in substantial improvements in accuracy. The apparent contradiction can be resolved with recourse to the machine learning concepts of training error-in our case, the geometric error for the set of corresponding points on which the homography is estimated-and generalisation error-in our case, the geometric error evaluated on other corresponding points that belong to the same planar structure.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, just because the residual error for consistent homographies may be slightly higher does not mean that consistent homographies are less accurate. On the contrary, experiments conducted in [8,9,32] demonstrate that enforcing consistency results in substantial improvements in accuracy. The apparent contradiction can be resolved with recourse to the machine learning concepts of training error-in our case, the geometric error for the set of corresponding points on which the homography is estimated-and generalisation error-in our case, the geometric error evaluated on other corresponding points that belong to the same planar structure.…”
Section: Discussionmentioning
confidence: 93%
“…Extensive simulations on synthetic data reported in [5,8,9,32,36] have already demonstrated that enforcing consistency constraints leads to more accurate homography estimates. Therefore rather than repeat similar simulations, we instead chose to investigate whether compatibility constraints are violated on typical real-world datasets.…”
Section: Experiments On Real Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, finding suitable initial values for the latent variables is a non-trivial task. The initialisation methods utilised by Chojnacki et al [10,11] and Szpak et al [35] are based on factorising a collection of homography matrices. The factorisation procedure is described in detail in [11,Sect.…”
Section: Introductionmentioning
confidence: 99%